The last kids on earth and the forbidden fortress eaudiobook - Brallier, Max (Last Kids on Earth, 2022)
The highly-anticipated eighth book in the #1 New York Times , Wall Street Journal , and USA Today bestselling series, with over 10 million copies in print! Picking up after Quint and Dirk's Hero Quest , the Last Kids are happily reunited—but quickly faced with a monstrous new mission. Inside an other-dimensional fortress, the evil Thrull, alongside a vile new villain, is carrying out a sinister plan. Jack, Quint, June and Dirk must make their own plans to infiltrate the stronghold before Thrull gets any closer to completing the mysterious Tower, a structure that could ultimately spell doom for this dimension.